"New Aspect of Living" a medium in the stage model recovery of Yolanda survivors - Domingo, June Royce V.; Garcio, Arah O.; Olaybar, Arianne Joy S. (2015)
The acquisition of a New Aspect of Living (NAoL) after a stressful event is one of the concepts that are not well-explored in the discipline of social sciences, particularly in the context of the Philippines. Furthermore, past researches suggest that NAoL is an end in itself which appears during the stage where an individual recognizes himself/herself to be recovered from a stressful event. However, this research seeks to examine the presence of a new aspect of living as embedded in the recovery period of an individual after having experienced a stressful event such as Typhoon Yolanda. A purposive sampling technique was employed in order to identify the participants of this study. Series of interviews were conducted to generate data which were then subjected to thematic analysis. The results revealed that the acquisition of a new aspect of living such as the formation of new relationship, developing one's spirituality, getting a new job, forming new social and leisure activities as a hobby, or the formation of new goals was able to aid in the recovery of an individual in such a way that it gave them the time to reconcile with the self, to grow as a person and to widen their perspective, resulting to their personal growth.
Undergraduate thesis (B.A. Psychology)--University of the Philippines, Tacloban
Keywords: New Aspect of Living (NAoL).; Typhoon Yolanda